2017
DOI: 10.1002/smll.201604179
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Growth of Millimeter‐Size Hexagonal Boron Nitride Single‐Crystal Domains on Epitaxial Nickel Thin Film

Abstract: Atomically thin hexagonal boron nitride (h-BN) is gaining significant attention for many applications such as a dielectric layer or substrate for graphene-based devices. For these applications, synthesis of high-quality and large-area h-BN layers with few defects is strongly desirable. In this work, the aligned growth of millimeter-size single-crystal h-BN domains on epitaxial Ni (111)/sapphire substrates by ion beam sputtering deposition is demonstrated. Under the optimized growth conditions, single-crystal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 46 publications
(84 reference statements)
1
75
3
Order By: Relevance
“…The domain size is mostly less than 100 micrometers. Reports on h-BN domains with a size close to one millimeter are rare [9,10]. Although wafer-scale single crystals have been reported through the coalescence of identically aligned h-BN domains [11], on twin-free single-crystal Rh (111) thin films [12], and on low-symmetry Cu (110) vicinal surface [13], it is noted that discrete h-BN domains or flakes over one millimeter have not been reported, and the understanding of the growth dynamics remains elusive.…”
mentioning
confidence: 99%
“…The domain size is mostly less than 100 micrometers. Reports on h-BN domains with a size close to one millimeter are rare [9,10]. Although wafer-scale single crystals have been reported through the coalescence of identically aligned h-BN domains [11], on twin-free single-crystal Rh (111) thin films [12], and on low-symmetry Cu (110) vicinal surface [13], it is noted that discrete h-BN domains or flakes over one millimeter have not been reported, and the understanding of the growth dynamics remains elusive.…”
mentioning
confidence: 99%
“…Although Cu‐Ni alloys can decrease the nucleation density of h‐BN, the corresponding maximum grain size is still limited to ≈100 µm . As far as we know, the maximum h‐BN domain sizes are in several hundreds of micrometers and can be achieved on Si‐doped Fe substrates, Ni (111) films or in Cu enclosures …”
mentioning
confidence: 99%
“…Considering the fast growth of single large domain on Si‐doped substrate as shown in Figure c, the high growth speed suggests the edge attachment is accelerated by the silicon dopant, probably via dehydrogenation of the aminoborane or passivated edge, and thus brings the growth mode into diffusion‐limited regime. Besides, silicon has been suggested to promote the dehydration of borazine on Cu and facilitate the catalytic growth of h‐BN, providing more B‐N source . Here, we performed first‐principle calculations on the dehydrogenation process as schematically illustrated in Figure S7 in the Supporting Information.…”
mentioning
confidence: 99%
“…The B 1s peak was observed near 190.1 eV for films deposited at 850 °C, which is consistent with sp 2 bonded BN reported in the literature, whereas BN films deposited at RT exhibited a B 1s peak near 190.8 eV, which is more consistent with sp 3 bonded c‐BN. However, the appearance of a loss feature at 199 eV in all films due to π–π* transitions is indicative of sp 2 bonding, and so even films with B 1s peaks at higher binding energies may contain a substantial fraction of sp 2 bonded BN.…”
Section: Resultsmentioning
confidence: 97%
“…It has repeatedly been shown that polycrystalline flakes of h‐BN can be grown with a typical film thickness <10 monolayers, and these flakes can be transferred from the growth substrate to other surfaces with minimal damage . Recently, large millimeter‐sized h‐BN domains grown by ion beam sputtering on Ni substrates has been reported, and it is apparent that minimization of defects on the substrate is key to achieving large enough domains for electronic applications.…”
Section: Introductionmentioning
confidence: 99%